In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children--The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis